Molecular Detection of bla OXA-48 Gene Encoding Carbapenem Resistance Pseudomonas aeruginosa Clinical Isolates from Khartoum State Hospitals, Sudan - Ali, Doha Omer; Arbab, Mohamed Hussein; Ahmed, Nagla Mohamed (مجلة الجزيرة للعلوم الصحية; مجلد 2 عدد 16 (2020), 2021)
Background: Carbapenem resistance in Pseudomonas aeruginosa is particularly worrisome because this class of β-lactam represents the last therapeutic resource for control of bacterial infection. Objectives This study aimed to detect the frequency of bla OXA-48 resistance gene among Pseudomonas aeruginosa clinical isolates during the period from November 2018 to November 2019. Methods: Hundred Pseudomonas aeruginosa clinical isolates, 81 carbapenems (imipenem meropenem) resistant and 19 carbapenems sensitive were collected from Omdurman Teaching Hospital, Fedail Hospital and Soba Teaching Hospital in Khartoum State-Sudan. All isolates were re-identified using conventional bacteriological techniques, their susceptibility to carbapenems were tested using Kirby-Bauer method for confirmation. All isolates were investigated for the presence of the bla OXA-48 gene using conventional PCR technique. Results: 60 (60.0%) out of 100 Pseudomonas aeruginosa clinical isolates were positive for blaOXA -48 gene. Out of 81 carbapenem resistant isolates 54(66.7%) were positive for bla OXA-48 gene, while among the (19) carbapenem sensitive isolates 6 (31.6%) were positive for blaOXA-48 gene. There was statistically significant association between carbapenem resistant isolates and the presence of bla OXA-48 gene ( P-value = 0.006). Wound swabs were the predominant clinical samples detected harboring bla OXA-48 gene both among the sensitive 5 (83.3%) and carbapenem resistant isolates 29(53.7) (P.value> 0.05). Conclusion: Our findings revealed high frequency of bla OXA-48 among carbapenem resistant isolates so identification of bla OXA-48 producing strains and taking efforts to reduce the rate of transferring these gene between the different strains is essential for optimization of  therapy and improves of patients outcomes.